2017
DOI: 10.4172/2327-5162.1000252
|View full text |Cite
|
Sign up to set email alerts
|

Meteorosensitivity in a Group of Patients Affected by Multiple Sclerosisand Hospitalized in a Rehabilitation Facility: An Observational Study

Abstract: Background: In the recent decades, the relationship between psycho-physical disorders and weather conditions has taken on an increased scientific solidity. Furthermore, it is known to every clinician that healthcare practice has an important role in the management of psycho-physical disorders of patients affected by multiple sclerosis. Given that meteorosensitivity is related to the psycho-physical feebleness, this study is an attempt to clarify if treatments in a non-acute care rehabilitation centre can reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Meteorological factors and other stressors may cause a challenge to the human physiological balance. When the balance is difficult to maintain, the development of somatic symptom disorder may be observed [20].…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological factors and other stressors may cause a challenge to the human physiological balance. When the balance is difficult to maintain, the development of somatic symptom disorder may be observed [20].…”
Section: Introductionmentioning
confidence: 99%
“…While climate adaptability can only be improved upon with more time spent in a given area, an Italian study noted that climate susceptibil-ity ('meteorosensitivity') can be improved upon with specific behavioral changes. Thus, the latent effects of ambient meteorological conditions on risk for MS may be partially modifiable [40]. In our study, SD of temperature increased MS visit risk most strongly within the LMW, UMW, NE, and DSW regions.…”
Section: Discussionmentioning
confidence: 54%
“…Our results suggest that cyclothymic and anxious temperaments, in particular, may contribute to increased sensitivity to weather phenomena and affect the severity of meteoropathy symptoms, including insomnia. As Freti et al (2017) suggested, meteorosensitive subjects display some difficulties in coping with psychophysical perturbations arising from meteorological events. According to the authors, the action of meteorological factors and other stressors can make maintaining a balance of physiological variables difficult.…”
Section: Discussionmentioning
confidence: 98%
“…According to Mazza et al (2012), meteorosensitivity describes the individually differing susceptibility to the impact of meteorological events that may, to a varying degree, cause new mental and somatic disorders or lead to the worsening of existing maladies. Freti et al (2017) asserted that human psychophysical reactivity (i.e. meteorosensitivity) and the ability to manage psychological stress affect the development of meteoropathy.…”
Section: Introductionmentioning
confidence: 99%